The Effect of "MOLKESPRO" Educational Media on The Level of Knowledge of Early Adolescents about Reproductive Health - Ulfa Nur Khasanah; Sheilla Tania Marcelina; Herawati Mansur (EMBRIO: Jurnal Kebidanan, 2024)
Child marriage in Indonesia is a recurring reality in society. Early marriage is a form of gender inequality, especially for women. Globally, 21 percent of women living in 2020 were married before the age of 18, and 12 million girls under 18 are married each year, or about 23 girls married as children every minute. Various reasons for the high rate of early marriage are not only due to educational, economic, and stigmatizing factors but also due to the low understanding of adolescents about reproductive health, which causes adolescents to have no choice, especially for adolescent girls. The purpose of this study was to determine the effect of "MOLKESPRO" monopoly media on adolescents' knowledge about reproductive health. The design of this study was pre-experimental with a pre-post-test design approach. Using the purposive sampling technique, the population was grade 6 elementary school students, as many as 31. In this study, the instrument used was a questionnaire about reproductive health—data analysis using a paired t-test. The results showed that the respondents' knowledge got the less category (35 percent) before being given health education and got a good knowledge category (81 percent) after being given health education. The results obtained p value less than 0.000 (0.000 less than a). Therefore, there is an effect of "MOLKESPRO" on the knowledge of early adolescents about reproductive health. Thus, the "MOLKESPRO" monopoly media can be used by midwives and other health workers in providing health education to early adolescents related to reproductive health, this is because its attractive design can make students enthusiastic to learn materials about reproductive health using the atmosphere created with fun.